LEXICAL-SEMANTIC GROUPS OF THE LEXICON OF KARLUK-TYPE UZBEK DIALECTS - Yakubov Sadigjon Latif ugli (International Journal of Literature and Language Studies, 2026)
This article provides a systematic analysis of the lexical-semantic groups of the lexicon of Karluk-type Uzbek dialects. The study classifies the vocabulary found in dialects belonging to the Karluk dialect system according to their meanings and identifies their semantic fields. Based on the thematic classification of lexical units, groups related to everyday life, natural phenomena, human activities, social relations, and cultural-ethnographic layers are examined separately. In addition, the historical development of dialect vocabulary and its relation to other Turkic languages are briefly discussed. The results of the study contribute to a deeper understanding of the lexical-semantic system of Karluk-type Uzbek dialects, the identification of their areal features, and the development of Uzbek dialectology.